Die selfbekendstelling van God in eksodus 3 en die betekenis daarvan vir vandag - Helberg, J. L. (Koers, 1988)
This article shows the perspective in which questions about the revelation of God, Scripture, the Name Yahweh, the land of Israel, theologies of liberation, material prosperity, et cetera should be asked and answered, and concentrates on the aspect of divine revelation and of the Name Yahweh, especially in connection with the divine self-identification to Moses. Exodus 3 puts everything in a theocentric perspective. The Old Testament religion is a re ligion of revelation, with a strong corrective towards human initiative, thought, attitude and activity. These matters have important implications for the approach to the Scriptures. The theocentric character of this religion implies that matters such as covenant, the Name Yahweh and the land not only have much im portance but are also relativised.